2022
DOI: 10.1186/s40634-022-00558-9
|View full text |Cite
|
Sign up to set email alerts
|

Mobile medial pivot (lateral slide) type total knee arthroplasty exhibits a medial pivot pattern: three-dimensional motion analysis using cadaveric knees

Abstract: Purpose The purpose of this study was to analyze the dynamic kinematics of the mobile medial pivot-type total knee arthroplasty (MMPTKA) using the three-dimensional (3D)-to-2D registration technique. Methods Cadaveric knees from five humans were used. Computed tomography of the lower limb and preoperative 3D planning for MMPTKA were performed. After performing TKA, passive motion of the knee was observed from a fully extended position to maximum fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The mobile insert exhibited little rotation or external rotation similar to that of the femoral component during knee flexion under the in vivo weight‐bearing condition during squatting, whereas the mobile insert exhibited internal rotation opposite to that of the femoral component during knee flexion under anaesthesia. This motion was similar to the results of the cadaveric study [24]. Regarding the femoral component, the amount of posterior translation of the medial and lateral sides under anaesthesia was greater than during squatting (i.e., in vivo weight‐bearing).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mobile insert exhibited little rotation or external rotation similar to that of the femoral component during knee flexion under the in vivo weight‐bearing condition during squatting, whereas the mobile insert exhibited internal rotation opposite to that of the femoral component during knee flexion under anaesthesia. This motion was similar to the results of the cadaveric study [24]. Regarding the femoral component, the amount of posterior translation of the medial and lateral sides under anaesthesia was greater than during squatting (i.e., in vivo weight‐bearing).…”
Section: Discussionmentioning
confidence: 99%
“…The movement of the axial rotation of the femoral component relative to the mobile‐bearing insert exhibited little rotation [28]. However, a previous cadaveric study using MMPTKA showed an opposite rotation of the insert relative to the femoral component and concluded that the shape of the inserts with high medial constraint and asymmetrical medial and lateral surfaces may be a major factor for this motion [24]. In this study, the insert showed opposite rotation relative to the femoral component under anaesthesia, as in the cadaveric study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations